2017
DOI: 10.1089/tmj.2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

American Telemedicine Association: Telestroke Guidelines

Abstract: The following telestroke guidelines were developed to assist practitioners in providing assessment, diagnosis, management, and/or remote consultative support to patients exhibiting symptoms and signs consistent with an acute stroke syndrome, using telemedicine communication technologies. Although telestroke practices may include the more broad utilization of telemedicine across the entire continuum of stroke care, with some even consulting on all neurologic emergencies, this document focuses on the acute phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 15 publications
0
67
0
2
Order By: Relevance
“…The World Health Organisation defines telemedicine as "the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, research and evaluation, and for the continuing education of health care providers, all in the interests of advancing the health of individuals and their communities" [20]. Previous work has demonstrated the feasibility of using telemedicine to assist with the clinical care of patients with a wide spectrum of neurological conditions including stroke [16,21,22], headache [23][24][25], multiple sclerosis [26], mental health disorders [27,28], epilepsy [29,30] and neurodegenerative diseases [31][32][33][34]. Although preliminary studies have suggested that telemedicine may be helpful in providing sideline and inoffice care to patients with concussion [35,36], there have been no studies that have examined the use of this technology to provide clinical care of paediatric concussion patients living in remote and medically underserviced communities in northern Canada.…”
mentioning
confidence: 99%
“…The World Health Organisation defines telemedicine as "the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, research and evaluation, and for the continuing education of health care providers, all in the interests of advancing the health of individuals and their communities" [20]. Previous work has demonstrated the feasibility of using telemedicine to assist with the clinical care of patients with a wide spectrum of neurological conditions including stroke [16,21,22], headache [23][24][25], multiple sclerosis [26], mental health disorders [27,28], epilepsy [29,30] and neurodegenerative diseases [31][32][33][34]. Although preliminary studies have suggested that telemedicine may be helpful in providing sideline and inoffice care to patients with concussion [35,36], there have been no studies that have examined the use of this technology to provide clinical care of paediatric concussion patients living in remote and medically underserviced communities in northern Canada.…”
mentioning
confidence: 99%
“…It also to empower change and innovation, can retool educational learning programs to lead to solutions, technological advancement, and higher standards. In addition, telemedicine association can mobilize its resources to effect transformation ( 44 - 50 ). That means boosting member engagement across various platforms, and refining internal operations to create a nimble, creative, and highly productive work culture.…”
Section: Discussionmentioning
confidence: 99%
“…One important aspect we seek to highlight is the question of how teleneurology services will be evaluated. Although telestroke has been available for almost 20 years 4 , it is only recently that a set of metrics for monitoring the effects of telestroke has been proposed 5 . With the variety of telestroke models available (for example, drip and ship, hub and spoke, etc.…”
Section: Competing Interestsmentioning
confidence: 99%